Amorphous Copper‐modified Gold Interface Promotes Selective CO2 Electroreduction to CO. Issue 13 (5th May 2022) - Zhan, Peng; Yang, Shuai; Chu, Mengen; Zhu, Qian; Zhuang, Yan; Ren, Cong; Chen, Ziyi; Lu, Lu; Qin, Peiyong
Abstract: Electroreduction of CO2 into valuable chemicals exhibits promising application potentials. Herein, a kind of nano‐porous AuCu foam which possesses amorphous copper (Cu)‐modified gold (Au) interface was designed for highly selective electroreduction CO2 into CO. As‐obtained Au0.95 Cu0.05 foam exhibits a Faradaic efficiency (FE) of 99.5 % for CO with a current density of 31.3 mA cm −2 . Compared with other Au‐based electrocatalysts, Au0.95 Cu0.05 foam shows a lower overpotential of 240 mV. The improvements in activity and selectivity of the AuCu foam might be attributed to the synergistic effect between the highly dispersed amorphous Cu and the matrix of Au. Detailed characterization indicates that the twisty nanowire morphology imparts multiple reactive sites on the electrode surface. The study demonstrates that amorphous Cu on the AuCu foam surface can boost CO2 activation by modifying the surface geometry and electronic structure. This finding provides a new strategy of modifying the metal interface to construct electrocatalyst. Abstract : Matrix : A kind of nano‐porous Au0.95 Cu0.05 foam which possesses amorphous copper‐modified gold interface was designed for selective electroreduction of CO2 into CO. A small amount of amorphous Cu on the matrix of Au can boost CO2 activation by modifying the surface geometry and electronic structure of the AuCu foam.